First Corinthians - Montague, George T. 1929- (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2011)
Cliques and the cross (1 Cor. 1) -- The power and the wisdom (1 Cor. 2) -- Our true boast is in God, not ministers (1 Cor. 3) -- Servants and stewards (1 Cor. 4) -- Cleansing the community (1 Cor. 5) -- The court and the courtesan (1 Cor. 6) -- Marriage and virginity (1 Cor. 7) -- Idols: freedom and conscience (1 Cor. 8) -- Paul's personal example (1 Cor. 9) -- Warnings and the Eucharist (1 Cor. 10) -- Problems in the community at worship (1 Cor. 11) -- Many gifts, one body (1 Cor. 12) -- Love, the heart of the gifts (1 Cor. 13) -- The gifts in practice (1 Cor. 14) -- The Resurrection (1 Cor. 15) -- Conclusion (1 Cor. 16).
"In this addition to the Catholic Commentary on Sacred Scripture (CCSS), a seasoned scholar interprets First Corinthians for pastoral ministers and lay readers alike. The CCSS series, which will cover the entire New Testament, relates Scripture to life, is faithfully Catholic, and is supplemented by features designed to help readers understand the Bible more deeply and use it more effectively in teaching, preaching, evangelization, and other forms of ministry. About the SeriesThe Catholic Commentary on Sacred Scripture (CCSS) responds to the desire of Catholics to study the Bible in depth and in a way that integrates Scripture with Catholic doctrine, worship, and daily life. The series will include seventeen volumes, offering readable, informative commentary on each book of the New Testament. The CCSS implements the theological principles taught by Vatican II for interpreting Scripture 'in accord with the same Spirit by which it was written'--that is, interpreting Scripture in its canonical context and in the light of Catholic tradition and the analogy of faith (Dei Verbum 12). The CCSS is packed with features designed to help readers use the Bible more effectively in teaching, preaching, evangelization, and other forms of ministry. Each volume provides exegesis as well as reflection and application sections. A set of cross-references links each passage to the Catechism, the Lectionary, and related biblical texts. Sidebars present information on the background of the text and on how the text has been interpreted by the Church. Abundant quotations from saints and Church Fathers enable readers to glimpse the continuity of Catholic tradition. Each volume includes a Glossary, a list of Suggested Resources, an Index of Pastoral Topics, and an Index of Sidebars"--Publisher description
Includes bibliographical references and indexes
Keywords: Bible -- Commentaries; Bible; Commentaries; Kommentar